Contemporary Painting as Reflector of Yoruba Cultural Values - Michael Olusegun Fajuyigbe (Yoruba Studies Review)
Every art form reflects the values of the cultural background that produces it, and visual culture in its present state is based on art and values from the past. This paper, therefore, examines the re-invention of culture and distinctive cultural ideals in contemporary Nigerian art. Specifically, it pinpoints contemporary Yorùbá paintings as visual markers of the Yorùbá value system. The study traces the origin of painting in Africa, from its earliest forms in African caves, shrines, and palaces, through the colonial and postcolonial eras to the present. Based on their contexts, eight (8) paintings that portray specific values of the Yorùbá and are ingrained with symbolic motifs, patterns and imageries are selected. Formal and contextual methods in art history are employed in the analysis of the data. The selected paintings serve as a visual document of the Yorùbá belief system; while contemporary Yorùbá artists are shown to consistently draw from their culture and design resources to establish a connection between the past and the present. The paper concludes that contemporary Nigerian art, generally, reveals new perspectives and meanings regarding art, culture, and identity in a fast-changing, multi-ethnic society like Nigeria